SURGICAL THERAPY OF UNUSUAL CONGENITAL CORNEAL FIBROMA - Hayat, Khizar; Shahzad, Muhammad; Lin, Zhang; Miao, Li; Xue, Sun Nai (Journal of Ayub Medical College Abbottabad, 2010)
Surgical removal of left congenital limbo corneal mass by peripheral lamellar keratoplasty (LKP) using preserved remaining corneasclera graft from other recipient was effective for the treatment of limbocorneal fibroma. A case of 17 year old Chinese girl with a corneal mass since her birth on 4:00 ’O clock position showed a size of about 2-3 mm. The patient was treated with total resection of the mass with part of Corneascleral Limbus and partial cornea with adjacent tissue and was diagnosed as fibroma after histopathology examination. After follow-up for 6 month, the vision and eye ball movements were normal and the graft was in normal position. Keywords: Congenital, Lamellar Keratoplasty, Fibroma, Refraction, Cosmetic